Synthesis and analytical characterization of monoazo bifunctional reactive dyes on cotton - U.G, Bashir; M. G, Sani; B.A, Aliyu; A, Umar; H, Zainab (Faculty of Applied Sciences, 2025)
In this study, two mono dichlorotriazinyl reactive dyes were synthesized. The synthesis involved diazotization, coupling with 1- naphthol-8-amino3-6-disulphomic acid (H-acid), and condensation with cyanuric chloride. The reactive dyes were applied on grey cotton fabric to assess dyeing performance. Spectrophotometric studies were carried out to investigate the wavelength of maximum absorption (λmax)—the percentage dye exhaustion, effects of temp. pH and duration of dyeing of the dyed samples were evaluated. The resultant dyes were characterized using standard spectroscopic methods. The results of the spectrophotometric analysis revealed that the λmax of the two dyes were 590mm and 600nm for dye (a) and (b), respectively. The wavelength of maximum absorption of the dyes in ethanol, water, and acetone was 600nm and 590nm for dye (a) and 600, 570, and 480nm for (b). The %dye exhaustion was 70 – 80%, and the fastness rating was very good and excellent.